STRUCTURAL TRANSFORMATIONS IN AXILLARY AND MESENTERIC LYMPH NODES IN CHEMOTHERAPY AND SURGICAL TREATMENT OF EXPERIMENTAL MAMMARY TUMOR - O. V. Kazakov; A. V. Kabakov; A. F. Poveshchenko; T. V. Rayter; D. N. Strunkin; A. P. Lykov; V. I. Konenkov (Сибирский научный медицинский журнал, 2019)
Was conducted histological study axillary and mesenteric lymph nodes in breast cancer induced by intramammary administration of N-methyl-N-nitrosourea, chemotherapy according to the CMF scheme (cyclophosphamide, methotrexate, 5-fluorouracil), operative removal of breast tumors (6.5 months from the beginning of the experiment). The results of the study. At chemotherapy of breast cancer, compared with the group with breast cancer without treatment, there was a decrease in the number of tumor cells in the axillary lymph nodes in comparison with mesenteric lymph nodes. The decrease in the area of the paracortical zone and the area of secondary lymphoid nodes remain in the axillary lymph nodes, in comparison with breast cancer without treatment. The reduction of the paracortical zone square remains in mesenteric lymph nodes. The area of lymphoid nodules with germinative centers decreases. The number of postcapillary venules with high endothelium and the number of macrophages in structural zones grow down. In the axillary lymph nodes after surgical treatment of breast cancer and chemotherapy in comparison with the treatment of breast cancer only with cytostatics, there is decrease in the area of the paracortical zone (with an increase in the number of small lymphocytes) and medullare cords. The area of lymphoid nodules with germinative and without germinative centers increases. In mesenteric lymph nodes, drainage function is reduced, increased the area of the paracortical zone, reduced the areas of lymphoid nodules with germinative centers and medullare cords (increased proliferative activity of cells), macrophage reaction in the cortical substance was revealed. Conclusion. The severity of structural transformations in cytoarchitectonics of the axillary and mesenteric lymph nodes depends on the treatment method.